Distinct topological properties of cue-evoked attention processing network in persisters and remitters of childhood ADHD. (December 2018) - Luo, Yuyang; Schulz, Kurt P.; Alvarez, Tara L.; Halperin, Jeffrey M.; Li, Xiaobo
Abstract: Attention deficit/hyperactivity disorder (ADHD) is a highly prevalent and impairing neurodevelopmental disorder that persists into adulthood in a sizeable portion of afflicted children. The persistence of ADHD elevates the risk for adverse outcomes that result in substantial individual and societal burden. The objective of this study is to assess neurobiological substrates associated with variability of clinical outcomes in childhood ADHD, which has considerable value for the development of novel interventions that target mechanisms associated with recovery. A total of 36 young adults who were diagnosed with ADHD combined-type during childhood and 33 group-matched controls were involved in the study. Adults with childhood ADHD were further divided into 17 persisters and 19 remitters based on DSM-5 criteria. Functional magnetic resonance imaging data during a cue-evoked attention task were collected from each subject. The cue-evoked attention processing network was constructed using graph theoretic techniques. Network properties, including global-, local-, and nodal-efficiency, and network hubs were computed. Group comparisons of the network properties were conducted. Significantly lower nodal efficiency in right inferior frontal gyrus and reduced left side frontal-parietal functional interactions were observed in both remitters and persisters relative to the controls. The ADHD persisters showed a unique pattern of significantly lower nodal efficiency in right middle frontal gyrus (MFG) and hyper-interactions between bilateral MFG. This study suggests that right MFG functional impairments may relate to inactive fronto-parietal functional interactions for sensory and cognitive information processing and symptom persistence in young adults with childhood ADHD.